Size of Left Cardiac Chambers Correlates with Cerebral Microembolic Load in Open Heart Operations - Elena Z. Golukhova; Anna G. Polunina; Svetlana V. Zhuravleva; Natalia P. Lefterova; Alexey V. Begachev (Cardiology Research and Practice)
Background. Microemboli are a widely recognized etiological factor of cerebral complications in cardiac surgery patients. The present study was aimed to determine if size of left cardiac chambers relates to cerebral microembolic load in open heart operations. Methods. Thirty patients participated in the study. Echocardiography was performed in 2-3 days before surgery. A transcranial Doppler system was used for registering intraoperative microemboli. Results. Preoperative left atrium and left ventricular end-systolic and end-diastolic sizes significantly correlated with intraoperative microembolic load (𝑟s=0.48, 0.57 and 0.53, 𝑃s≺.01, resp.). The associations between left ventricular diameters and number of cerebral microemboli remained significant when cardiopulmonary bypass time was included as a covariate into the analysis. Conclusions. The present results demonstrate that increased size of left heart chambers is an influential risk factor for elevated cerebral microembolic load during open heart operations. Mini-invasive surgery and carbon dioxide insufflation into wound cavity may be considered as neuroprotective approaches in patients with high risk of cerebral microembolism.